Performance of the Penha CLM-350 corn combine: part I - ear picking system - Furlani Jr, J.A.; Guimarães Jr, J.B.; Balastreire, L.A. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1977)
This work was designed with the aim of evaluating the performance of the Penha CLM-350 corn combine, to furnish data to designers and users. The efficiency of the ear picking system was studied, and the percentage of the harvested corn was determined for the various treatments considered. A dimensionless U parameter was defined as the ratio between the peripheral speed of the snapping rolls and the speed of the harvester. The U terms were related to the percentages of corn harvested and corn lost on the ground. The analysis of variance with the F test at 1% and 5% probability levels was utilized to analyse the data, and Tukey's test was utilized for comparison between means. The statistical analysis showed that the treatment were not significant for the percentage of harvested corn, the efficiency maintained above 84,42% for the test conditions. For the conditions tested the values were limited by mechanical characteristics of the combine, particularly the transmission ratio. This suggests the design of a mechanism, which should provide the possibility of changing the transmission ratio from the tractor power take-off to the snapping rolls. This would provide a wider range of variation for U and could provide a mathematical relationship with efficiency.